GROSS ANATOMY OF STERNUM IN WHITE-BREASTED WATERHEN (AMAURORNIS PHOENICURLUS) - J. Violet Beaulah; P. Sridevi; T.A. Kannan; Geetha Ramesh; S. Ushakumary (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Gross anatomy of sternum in white-breasted waterhen was studied. Bone samples (sternum) were collected from three carcasses of white-breasted waterhen died were brought for postmortem examination to the Department of Veterinary Pathology, Madras Veterinary College, Chennai. The sternum was quadrilateral in shape. The longitudinal groove on the body of the sternum extended proximally and disappeared distally. The antero-lateral process was large, three-sided polygon shaped. Postero-lateral process was clamp-like at its posterior end. Postero-lateral process extended beyond the level of body of the sternum. Foramen ovale wasnoticed in the form of a W- shaped oval notch between the body of the sternum and the postero-lateral process. The anterior border of body of the sternum was noticed with two medial pneumatic notches.